Field experiments of Anopheles gambiae attraction to local fruits/seedpods and flowering plants in Mali to optimize strategies for malaria vector control in Africa using attractive toxic sugar bait methods - Müller, Günter C (BioMed Central, 2010)
BACKGROUND: Based on recent studies in Israel demonstrating that attractive toxic sugar bait (ATSB) methods can be used to decimate local anopheline and culicine mosquito populations, an important consideration is whether the same methods can be adapted and improved to attract and kill malaria vectors in Africa. The ATSB approach uses fruit or flower scent as an attractant, sugar solution as a feeding stimulant, and an oral toxin. The ATSB solutions are either sprayed on vegetation or suspended in simple bait stations, and the mosquitoes ingesting the toxic solutions are killed. As such, this approach targets sugar-feeding female and male mosquitoes. This study examines the attractiveness of African malaria vectors to local fruits/seedpods and flowering plants, key biological elements of the ATSB approach for mosquito control. METHODS: Three field experiments were conducted at sites in Mali. The attraction of Anopheles gambiae s.l. to 26 different local fruits and seedpods was determined at a site in the semi-arid Bandiagara District of Mali. Wire mesh glue traps with fruits/seedpods suspended on skewers inside were set along a seasonal lagoon. Seven replicates of each fruit/seedpod species were tested, with a water-soaked sponge and a sugar-soaked sponge as controls. The attraction of An. gambiae s.l. to 26 different types of flowering plants was determined at a site near Mopti in Mali. The flowering plants held in a water-filled buried container were tested using the same glue traps, with controls including water only and sugar solution. Six replicates of each selected plant type were tested on transects between rice paddies. Additional studies using CDC light traps were done to determine the relative densities and periodicity of An. gambiae s.l. attraction to branches of the most highly attractive flowering plant, branches without flowers, human odor, and candescent light. RESULTS: Of the 26 fruits and seedpods tested, 6 were attractive to An. gambiae s.l. females and males, respectively. Guava (Psidium guajava) and honey melon (Cucumis melo) were the two most attractive fruits for both females and males. Of the 26 flowering plants tested, 9 were significantly attractive for females, and 8 were attractive for males. Acacia macrostachya was the most attractive flowering plant. Periodicity studies using this plant showed peaks of An. gambiae s.l. attraction between 1930 and 2200 h and 0400-0500 h, which differed considerably from the response to human odors, which expectedly peaked at around midnight. CONCLUSION: These field experiments in Mali highlight that female and male An. gambiae s.l. have pronounced differences in attraction for diverse types of indigenous fruits/seedpods and flowering plants. The identification of attractive fruits and seedpods shows that a variety of indigenous and locally abundant natural products could potentially be used as juices to make ATSB solution for mosquito control. As well, the simple methods used to identify the most attractive flowering plants provide valuable insights into the natural history of sugar feeding for An. gambiae s.l. These observations can be used to guide future strategies for employing ATSB methods for malaria vector control in Africa. They also provide a basis for subsequent chemical analysis and development of attractive baits for mosquito control.